INTELIGENSI DAN BAKAT SERTA IMPLIKASINYA DALAM PEMBELAJARAN - abdulah, abdulah (Information Technology Education Department, 2021)
This study aims to determine the differences that exist in individuals viewed from the aspect of intelligence, talent and implications in learning. Individual differences are a gift given by God to humans, where between one individual and another there must be differences. It is very important for educators to understand the differences that exist in students. By knowing the causes that influence individual differences, educators can provide equal treatment to students. The method used is a literature study by processing and analyzing a number of relevant literature. Data were analyzed, grouped, and interpreted to determine the factors that influence individual differences. The results show that individual differences based on intelligence, talent in learning are a concern for educators in developing the potential that exists in students, this needs to also be supported by parents of students so that students are more enthusiastic in learning, channeling the talents of students, and how to respond to individual differences who have different intelligence and talents in learning in the school environment.